The features of women's criminal liability under the legislation of the Russian Federation, the Republic of Kazakhstan and the Republic of Chad: comparative legal aspect - Abdulvaliev, А.Ф.; Muratkhanova, М.Б.; Abdoulaye, Н.Х. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article examines the comparative legal aspects of women's criminal liability under the legislation of the Republic of Chad, the Russian Federation and the Republic of Kazakhstan in the issue of sentencing. The relevance of the study is due to the lack of works containing a comparative analysis of domestic criminal legislation with foreign, differing in the applicable law – Islamic. The main method of scientific research was the comparative legal analysis of the criminal law norms of the three states. Methods of systematization and generalization were also used to structure the information received and formulate the conclusions reached by the authors. The authors concluded that, unlike the criminal legislation of the Russian Federation and the Republic of Kazakhstan, the criminal legislation of the Republic of Chad does not provide for any guarantees and indulgences for women, providing for them, along with men, a general rule of sentencing and joint detention while serving a sentence. Therefore, it is necessary to amend the Criminal Code of the Republic of Chad, affecting the issue of mitigating the criminal responsibility of women, as well as the place of detention while serving a sentence.